2018
DOI: 10.2196/11579
|View full text |Cite
|
Sign up to set email alerts
|

Creating Gameful Design in mHealth: A Participatory Co-Design Approach

Abstract: BackgroundGameful designs (gamification), using design pieces and concepts typically found in the world of games, is a promising approach to increase users’ engagement with, and adherence to, electronic health and mobile health (mHealth) tools. Even though both identifying and addressing users’ requirements and needs are important steps of designing information technology tools, little is known about the users’ requirements and preferences for gameful designs in the context of self-management of chronic condit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
75
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(93 citation statements)
references
References 51 publications
9
75
0
1
Order By: Relevance
“…Examples include cafés, airports, and train stations. Similarly, Jessen et al [ 22 ] used this approach while researching participatory design frameworks for a self-management app in a chronic disease population. They used common enjoyable games such as Super Mario, Crosswords, and Monopoly as a vehicle to elicit further thoughts for discussion on the concept of creating their design.…”
Section: Discussionmentioning
confidence: 99%
“…Examples include cafés, airports, and train stations. Similarly, Jessen et al [ 22 ] used this approach while researching participatory design frameworks for a self-management app in a chronic disease population. They used common enjoyable games such as Super Mario, Crosswords, and Monopoly as a vehicle to elicit further thoughts for discussion on the concept of creating their design.…”
Section: Discussionmentioning
confidence: 99%
“…This review found that little more than half do, according to their app store descriptions. Just as successful therapeutic outcomes of face-to-face therapy can be attributed to more than the theoretical framework—factors such as rapport with the therapist, therapist skills, and an individual’s motivation to change—so too are there other elements of a mental health app that may contribute to a successful therapeutic outcome, such as usability and ease of use, aesthetics, level of gamification, etc [ 65 , 69 ]. There would appear to be much research that still needs to be done on all these factors and how they interrelate with theoretical frameworks as well as whether certain factors mediate or moderate others.…”
Section: Discussionmentioning
confidence: 99%
“…Codesign is recognised as an important and effective approach for strengthening interventions that target healthcare practices. [64][65][66][67][68][69][70][71][72][73] Successful discharge communication in ED practice requires the active involvement of HCPs, parents or caregivers and patients. Including these relevant stakeholders in the design and usability testing of interventions to support discharge communication is particularly important given the interventions are likely to involve behaviour change.…”
Section: Discussionmentioning
confidence: 99%